Mobile Smart Presence Design On Regional Government Using Spiral Model - I Gede Sudiantara (International Journal of Engineering and Emerging Technology, 2021)
Attendance is an important routine that employees do before starting and leaving work. In addition, attendance is one of the benchmarks in measuring employee’s discipline. Employee’s discipline can affect employee’s performance appraisal. Discipline is also one of the references in the process of salary increases, promotions, demotions, and dismissal of employees. The attendance recording process can be implemented on smartphone devices. In this article, the author designs a smart presence system with spiral model. The spiral model stage that focuses on the approach to the client makes the system built according to the client's wishes. Evaluations from staff and users are also very helpful in improving the presence system in subsequent developments.